ULAMA DAN POLITIK Tinjauan Peran Abdurrahman Wahid Dalam Perpolitikan Indonesia - Henny Yusalia (Fakultas Dakwah dan Komunikasi, Universitas Islam Negeri, Raden Fatah Palembang, 2011)
Clergy involvement in politics is a political reality in Indonesia. It can not be removed from the dynamics of history and journey of this nation. One scholar who has a major influence is the KH Abdurrahman Wahid (Gus Dur). His figure is important because the political dynamics of Indonesia also can not be released from his position. In the new order, Gus Dur was heavily involved in the position of NU activists in Islamic organizations. Through these organizations, Gus Dur can enter the territory of Indonesia's political and participate in relationships with various other parties, especially the political figures who was still active.In the era of reform, Gus Dur precisely into the active region of practical politics by founding the National Awakening Party. Until eventually became president of Indonesia. Abdurrahman, the more shows that the activity of the clergy, as a religious leader, can not be separated from the role in the political realm. Indonesia's political and has its own distinctive characteristics, namely the dynamics and patterns have a close relationship between the clergy and politics